ASPECTS OF CHANGES OF RELATIONSHIPS WITH PARENTS: TEENAGERS’ VIEW - Aramavičiūtė, Vanda; Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2008)
The article raises the problem of teenagers’ attitudes to family in the context of globalisation. Having in mind globalization researchers’ viewpoint that globalization strengthens the relations of contemporary man with the world at large on the one hand, but on the other, it might weaken the relations with local communities (family, school and other institutions of micro-surroundings) and their separate members, the main attention is focused on teenagers’ attitude towards their relations with parents. The article also attempts to reveal teenagers’ evaluations of relationship with their teachers and friends as their close people and their relations with themselves. On the basis of longitudinal research data, the changes in teenagers’ attitude to their relationships are unfolded having taken place in the period of eight years. The comparison of senior (16–18) and younger (13–15) teenagers’ attitude to their relations with the above-mentioned people is also provided.